(3EOGQI GdTQGA hGdJNRjf (B:s (3eONd MOjK (B/s - (3Rhjda, egOj MSfs ((3YeGf(B: s (3OGQ GdacQ ddWHGYI hGdfTQ hGdJhRjY(B, s, 2002)
(3EOGQI GdTQGA(B-(3CSGSjGJ GdTQGA(B- (3CUhd GdYdejI ddTQGA(B- (3JNWjW fTGW EOGQI GdTQGA(B- (3Jbjje fTGW EOGQI GdTQGA(B-(3EOGQI GdJNRjf(B- (3eaGgje CSGSjI aj EOGQI GdeNGRf(B- (3GdJhUja hGdJHhjH hJQejR GdehGO(B- (3ELQGAGJ GdJNRjf(B- (3Jbjje COGI EOGQI GdJNRjfs
Keywords: (3GdJNRjfs; (3GdTQGAs